Transformasi Ajaran Pendidikan Agama Hindu Dalam Membangun Keseimbangan Intelek, Moral, dan Spiritual Siswa di UWP Vidya Wisata Kubutambahan - Raka, I Nyoman; Vivien Pitriani, Ni Rai (Jurnal Penelitian Agama Hindu, 2025)
This research aims to examine the transformation of Hindu religious teachings in fostering intellectual, moral, and spiritual balance among students at UWP Vidya Wisata Kubutambahan. The study employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, documentation, and focused group discussions with subjects including students, teachers, the principal, and Hindu religious education program managers. The findings indicate that the integration of Hindu religious values into the school schedule at UWP Vidya Wisata Kubutambahan is implemented through specific Hindu religious subjects, the application of values in other subjects, and extracurricular activities. Teachers play a crucial role in this transformation process through training and a holistic approach that combines cognitive, affective, and psychomotor aspects. The impact of integrating Hindu religious values is reflected in students' increased intellectual understanding of Hindu teachings, the strengthening of moral values such as honesty and responsibility, and spiritual balance characterized by heightened spiritual awareness and stress management abilities. However, the research also identifies challenges such as resistance to change, limited resources, and diverse student backgrounds that affect program implementation. Based on these findings, it is recommended to continue developing a curriculum that integrates Hindu values more comprehensively, enhance teacher training, and provide more supportive resources and facilities. This is expected to make the transformation of Hindu religious teachings more effective in building intellectual, moral, and spiritual balance among students at UWP Vidya Wisata Kubutambahan.